I'll make the list, you go to the store: dividing the labor in Canadian defence purchases. Issue 2 (4th May 2017) - MacMillan, Ian
Abstract: Problems with high-price military acquisitions are an ongoing phenomenon in Canada; the most recent being the so-called " reset" of the F-35. Indeed, expensive purchases in Canada are prone to delays, cost-overruns and cancellations, and generally fail to satisfy both defence needs and procurement-aided industrial ambitions. While factors such as industrial benefits affect timely and affordable deliveries, Canadian outcomes are generally due to an overlap of responsibilities between federal politicians and public servants. For all of the ink spilled discussing what should be procured and how partisan oriented governments block irrational military ambitions, there has only been one well-known attempt to approach the subject with theory. Conscious design brings clarity to a complex process by explaining the necessity of a division of labour in which a governing party sets objective policy goals and public servants follow a process to select instruments which match these goals.